GENEALOGI GERAKAN PENEGAKAN SYARI’AT ISLAM DI INDONESIA - Sodiqin, Ali (UIN Sunan Kalijaga Yogyakarta, 2015)
Enforcement of Islamic law in Indonesia has historically and empirically problem. Debating in this case is not a new discourse of Islamic law, but of a